AKTIVITAS CYBER PUBLIC RELATIONS ELMIKA HIJRAH MELALUI MEDIA SOSIAL - Rafika Hani; Yuliani Dewi Risanti (Jurnal Visi Komunikasi, 2023)
This research focused on the implementation of Cyber Public Relations activities through the use of social media. Cyber Public Relations activities are increasingly being carried out by Public Relations practitioners in line with the increasing internet users in Indonesia. The purpose of this study was to determine how the campaign activities carried out by Syar'i Muslim clothing companies through the implementation of Cyber Public Relations which focused on the use of social media through the stages of strategic communication planning. This research uses a qualitative case study method with data collection through observation, documentation and in-depth interviews with the owners and employees of the companies that are the research objects. The results showed that in campaign activities, the object under study had determined the values in Hijrah to be communicated in the implementation of Cyber Public Relations. In the communication media selection stage, the company uses social media Facebook, Twitter and finally focuses on using Instagram. As for measuring the effectiveness of the campaign, it has not been done optimally because it is only seen from the number of followers, likes, comments and shares obtained from each content uploaded on social media.